2017
DOI: 10.1002/jclp.22553
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation difficulties in obsessive‐compulsive disorder

Abstract: Results showed that emotion regulation difficulties in OCD cannot simply be attributed to mood difficulties. Theoretical and treatment implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
48
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 45 publications
9
48
2
1
Order By: Relevance
“…The hypotheses were largely supported by the data. As anticipated and in accordance with prior research (Berman et al, 2018;Fergus & Bardeen, 2014;Fernández de la Cruz et al, 2013;Leeuwerik et al, 2019;Wetterneck et al, 2013;Yap et al, 2018), symptom severity and obsessive beliefs were negatively correlated with self-compassion and positively associated with emotion regulation difficulties. In line with our expectation and previous studies (Finlay-Jones et al, 2015;Scoglio et al, 2018;Vettese et al, 2011), a strong and negative correlation between selfcompassion and difficulties in emotion regulation existed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The hypotheses were largely supported by the data. As anticipated and in accordance with prior research (Berman et al, 2018;Fergus & Bardeen, 2014;Fernández de la Cruz et al, 2013;Leeuwerik et al, 2019;Wetterneck et al, 2013;Yap et al, 2018), symptom severity and obsessive beliefs were negatively correlated with self-compassion and positively associated with emotion regulation difficulties. In line with our expectation and previous studies (Finlay-Jones et al, 2015;Scoglio et al, 2018;Vettese et al, 2011), a strong and negative correlation between selfcompassion and difficulties in emotion regulation existed.…”
Section: Discussionsupporting
confidence: 89%
“…Self-compassion was measured using the 12-item Self-Compassion English (Gratz & Roemer, 2004) and translated German version (Ehring, Fischer, Schnülle, Bösterling, & Tuschen-Caffier, 2008). One exception seems to be the awareness subscale (Bardeen, Fergus, & Orcutt, 2012;Hallion, Steinman, Tolin, & Diefenbach, 2018;Yap et al, 2018). As there is a growing consensus that the DERS total score is psychometrically stronger without the awareness items, we excluded this subscale from our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Fernández de la Cruz et al (131) showed that patients compared to controls had significantly higher scores on all subscales except for the "lack of emotional awareness scale." Similarly, Yap et al (135) found that OCD patients scored significantly higher than controls on all DERS subscales, and group differences remained significant after correcting for depression and anxiety on all scales except for the lack of emotional awareness and emotional clarity scales. These findings indicate that patients with OCD have difficulties regulating their emotions, specifically expressed in the tendency to show a nonacceptance of emotions, experienced difficulties in goal-directed behavior and impulse control when distressed, and the use of maladaptive regulation strategies.…”
Section: Emotion Regulationmentioning
confidence: 80%
“…Considering the significance, plenty of studies have been yielded in the recent years, focusing on emotional responses or experiences with the help of fMRI [4][5][6]. More neuroimaging studies concentrated on the emotions with negative valence induced by aversive stimuli, such as fear and disgust, to uncover the neural correlates underlying various psychiatric diseases, such as the obsessive-compulsive disorder (OCD), anxiety, and depressive disorders [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%